Anterior Cruciate Ligament Revision Using Quadriceps Tendon Autograft and Lateral Extra-Articular Tenodesis - Fabrizio Matassi, M.D.; Jacopo Corti, M.D.; Mattia Chirico, M.D.; Piero Franco, M.D.; Zyad Ayman Taha, M.D.; Roberto Civinini, M.D. (Arthroscopy Techniques)
Revision of anterior cruciate ligament (ACL) reconstruction presents numerous challenges not encountered in the primary setting and therefore requires thorough preoperative planning. Addressing tunnel widening is the primary concern, and therefore the appropriate graft choice is pivotal. Quadriceps tendon autograft recently has gained popularity for its dimensions and the possibility to harvest a bone block from the patella that can fill potential tunnel bone defects. Adjunctive procedures to isolated ACL reconstruction such as lateral extra-articular tenodesis (LET) may help in sharing the loads with the neoligament, with recent findings recommending LET in the revision setting. The technique presented in this Technical Note describes a 1-stage revision ACL combined with LET using a quadriceps tendon autograft with a bone plug.